Demands for productive factors in the maquiladora industry - Ibarra Salazar, Jorge; García Pérez, Francisco (Estudios Económicos de El Colegio de México, 2016)
Using a production function that does not impose separability and/or substitution restrictions among the productive factors (translog function), in this paper we estimate the demand of inputs of the maquiladora industry. We use data than combine annual time series (1990–2006) with cross section of nine economic sectors. We find that the own price elasticity of the demand of labor is in average slightly above one in absolute value (-1.03); that the demand of materials is below one in absolute value (-0.506); and that the own–price elasticity of capital is above one in absolute value (-2.21).